2014
DOI: 10.5808/gi.2014.12.4.187
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Metabolic Syndrome in Koreans

Abstract: Metabolic syndrome (METS) is a disorder of energy utilization and storage and increases the risk of developing cardiovascular disease and diabetes. To identify the genetic risk factors of METS, we carried out a genome-wide association study (GWAS) for 2,657 cases and 5,917 controls in Korean populations. As a result, we could identify 2 single nucleotide polymorphisms (SNPs) with genome-wide significance level p-values (<5 × 10-8), 8 SNPs with genome-wide suggestive p-values (5 × 10-8 ≤ p < 1 × 10-5), and 2 SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Efforts have been made to map the metabolicassociated single-nucleotide polymorphisms (SNPs) using a single component as the quantitative outcome [13][14][15][16][17][18][19]. Consider MetS as a binary outcome, several genome-wide association studies (GWAS) attempted to find susceptible genetic loci affecting multiple metabolic outcome [20][21][22][23][24]. From these studies, tagSNPs mainly including rs9939609 on FTO, rs629301 on SORT1, rs12678919 near LPL, rs1532085 on LIPC, rs651821 on APOA5, rs7412 on APOE, rs1532624 on CETP, rs671 on ALDH2, rs4607517 on GCK and other variants had been reported as metabolic-associated loci.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made to map the metabolicassociated single-nucleotide polymorphisms (SNPs) using a single component as the quantitative outcome [13][14][15][16][17][18][19]. Consider MetS as a binary outcome, several genome-wide association studies (GWAS) attempted to find susceptible genetic loci affecting multiple metabolic outcome [20][21][22][23][24]. From these studies, tagSNPs mainly including rs9939609 on FTO, rs629301 on SORT1, rs12678919 near LPL, rs1532085 on LIPC, rs651821 on APOA5, rs7412 on APOE, rs1532624 on CETP, rs671 on ALDH2, rs4607517 on GCK and other variants had been reported as metabolic-associated loci.…”
Section: Introductionmentioning
confidence: 99%
“…Candidate gene and whole exome sequencing studies have also identified mutations in patients with rare forms of MetS [16, 17]. Meta-analyses of genome-wide association studies (GWAS) in Europeans and Asians have reported associations between MetS and variants in or near several loci including ZPR1 , BUD13 , APOA5 , LPL , and CETP genes [1820]. …”
Section: Introductionmentioning
confidence: 99%
“…MetS is a disorder of energy utilization and storage, and it increases the risk of developing cardiovascular disease and diabetes. MetS includes multiple clinical traits including increased plasma glucose, abdominal obesity, dyslipidemia, and high blood pressure (Jeong et al, 2014). All current definitions of MetS include five clinical parameters in different combinations, namely: obesity, hypertriglyceridemia, low levels of high density lipoprotein, hypertension, and elevated levels of fasting glucose (Cohen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%